Comparison of augmented reality glasses for the assistive communication support of hearing loss - Rhodin, Helge; Ersoy, Imran; Aygun, Sefa; Pfeiffer, Christoph J.; Vollmer, Anna Lisa; Todt, Ingo (Frontiers in Neurology, 2025)
BackgroundAugmented reality (AR) glasses can be utilized for various medical applications. Primarily, a visual overlay on the optic screen offers additional operational information. A transfer of acoustic information via speech-to-text transcript using AR glasses presents a new non-surgical option to support patients with different forms of hearing loss. This study aimed to evaluate different AR glasses for speech-to-text transcription.MethodsWe compared four different AR glasses systems (Even Realities, G1; Meizu, MYVU IMIKI; XREAL, AIR, and Epson, Moverio 40) in terms of speech-to-text transcription, design, software, microphone and connection in this laboratory based study. Speech-capturing ability was tested using free-field numbers, monosyllables, and OLSA in quiet and in noise.ResultsThe AR systems achieved Freiburger monosyllabic speech recognition rates between 20 and 45% at 65 dB. OLSA in quiet results vary between 77 and 100%, with increases of +1.7 dB and +3.5 dB in noise. AR systems differ substantially in terms of design, software, microphone position, and connection. Proposed indication groups are given.ConclusionAR glasses provide a potential supportive tool for patients with specific indications suffering from hearing loss. The systems show limitations in challenging hearing situations.